Green ceramic machining benefits through ultrasonic-assisted turning: an experimental investigation - Júnior, Marcos Gonçalves [UNESP]; França, Thiago Valle [UNESP]; Fortulan, Carlos Alberto; da Silva, Rodrigo Henriques Lopes; Foschini, Cesar Renato [UNESP] (Springer Nature, 2022)
Machining of advanced ceramics in the green state aims to achieve complex geometry with near-net-shape dimensions minimizing machining steps after sintering, good surface finish, economic efficiency and flexibility, and reduced process costs, in addition to the removal of the outer layer with potential defects and prior correction of distortions expected during sintering. However, the pressure exerted by the cutting edge plus the removal of lumps can introduce damage such as chipping to the green part due to its low mechanical strength, especially with inappropriate cutting parameters. Ultrasonic-assisted machining on the cutting tool has been applied to improve machining performance by improving surface finish, reducing machining forces, and reducing tool wear. This paper proposes a study on ultrasonic-assisted turning (UAT) of ceramic materials in a green state where a flexure hinge was developed for allowing tool vibration only toward the depth of cut direction. A central composite design of experiments (DOE) with a full factorial design was performed to determine the proper condition of the cutting parameters. The results showed that the UAT on ceramic materials in a green state compared to conventional turning (CT) provided process benefits through improved surface finish due to reduced lump pull-outs, decreased tool flank wear by 34%, and reduced machining forces (10%). Finally, ultrasonic vibration promoted intermittent part-tool contact releasing the removed debris, which increases material removal at the chip-tool interface and consequently diminishes material adhesion on the tool.
Keywords: Advanced ceramics; Green machining; Machining forces; Ultrasonic-assisted turning